Pengaruh Latihan Box Jump, Box Shuffle, dan Squat Jump Terhadap Kekuatan Otot Tungkai Pada Atlet Ukm Badminton Universitas Negeri Malang - Saputra, Andriyan; Yunus, Mahmud; Pribadi, Heri Purnama (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2023)
To perform jump maneuvers such as smashes in badminton, good muscle strength is needed. In the development of strategy, mentality, tactics and techniques, strength plays a crucial physical role. Exercises that can increase leg muscle strength are plyometrics by: box jumps, box shuffles and squat jumps. The research aimed to find out whether the box jump, box shuffle, and squat jump training programs had an effect on UKM Badminton athletes at Malang State University. This study has a pre-experimental nature by using the One Group Pretest-Posttest Design. The research also used 15 athletes as subjects, and program training, with details of time three times per week for 18 meetings. The results prove that there is a significant value of 0.001 0.05, using the paired sample t-test, meaning that there is a significant effect from the treatment that has been given, if the value is significant (0.05) then the hypothesis can be accepted. Based on the results of the study, the final conclusion revealed that the treatment affected the flexibility of muscle strength in Athletes UKM Badminton UM.